PENGARUH KOMPENSASI, KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KUD MOJOSONGO Studi kasus pada KUD Mojosongo di Boyolali - WIDI ASTUTI, EVI; dasmadi, dasmadi; puji rahayu, listyowati (Universitas Boyolali, 2020)
This is study aims to determine and prove the influence of compensation, leadership and work discipline on employee performance at KUD Mojosongo. This research using quantitative research method with the collection of data through the technique of questionnaires. Sample used for this research is 30 employees of KUD Mojosongo by using samplingjenuh method. The technique analysis used is multiple linear regression with SPSS 20. Then, seeing how big influence the compensation, leadership and work discipline on employees performance on hypoesis test. From regression analysis tes, explained that 26,3% variables of compensation, leadership and work discipline on employees performance. Meanhile 73,7% influenced by other variables. Keywords : Compensation, Leadership, Work Discipline and Employees Perfomance.